Wadi'ah Savings in Islamic Financial Institutions: Compliance with Fatwa and Islamic Ethics: Tabungan Wadi'ah di Lembaga Keuangan Islam: Kesesuaian dengan Fatwa dan Etika Islam - Widyarini, Widyarini (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2024)
Abstract: This study aims to evaluate the implementation of Wadi'ah savings accounts managed by various Islamic Financial Institutions (LKS), both large and small. This evaluation is deemed necessary due to the frequent deviations from the Fatwa issued by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) in practice. As a financial product grounded in Islamic law and moral principles, the proper and accurate application of Wadi'ah savings is crucial to ensuring compliance with Shariah principles. This research employs a qualitative method with an analytical-philosophical approach, gathering primary data from the official websites of several randomly selected LKS. Given that LKS is an industry regulated by the Financial Services Authority (Otoritas Jasa Keuangan or OJK), the data obtained is homogeneous so it does not require a large sample. The findings of the study reveal that, firstly, some LKS continue to promise profit-sharing to depositors, despite this being inconsistent with the Wadi'ah principle. Secondly, many LKS still perceive the deposited goods as the nominal value of money rather than a trust (amānah) that must be managed with justice. Thirdly, there is an indication of unfair (ẓālim) practices and categorized as non-ethical behavior in Islam due to the absence of profit-sharing for depositors. Although some LKS have proposed solutions, these often violate existing regulations. Furthermore, the practice of Wadi'ah savings in Islamic Commercial Banks (Bank Umum Syariah or BUS) does not significantly differ from conventional savings, except in terms of profit-sharing, where BUS still imposes account opening fees on customers.   Abstrak: Penelitian ini bertujuan untuk mengevaluasi implementasi Tabungan Wadi’ah yang dijalankan oleh berbagai Lembaga Keuangan Syariah (LKS), baik besar maupun kecil. Evaluasi ini dianggap penting mengingat banyaknya penyimpangan terhadap Fatwa DSN MUI dalam praktiknya. Sebagai salah satu produk keuangan yang berlandaskan hukum dan moral Islam, pelaksanaan Tabungan Wadi’ah memerlukan penerapan yang benar dan sesuai dengan prinsip-prinsip syariah. Penelitian ini menggunakan metode kualitatif dengan pendekatan analitik-filosofis, data primer dikumpulkan dari website resmi beberapa LKS yang dipilih secara acak. Dengan catatan LKS merupakan industri yang diatur oleh Otoritas Jasa Keuangan (OJK), data yang diperoleh bersifat homogen sehingga tidak memerlukan sampel yang besar. Hasil penelitian menunjukkan bahwa, pertama, beberapa LKS masih menjanjikan bagi hasil kepada nasabah, meskipun hal ini tidak sejalan dengan prinsip Wadi’ah. Kedua, banyak LKS yang masih mempersepsikan barang yang dititipkan sebagai nilai nominal uang, bukan sebagai amanah yang harus dikelola dengan prinsip keadilan. Ketiga, terdapat praktik yang dianggap tidak adil (zalim) dan masuk dalam perilaku niretika dalam Islam, karena tidak adanya bagi hasil kepada nasabah. Meskipun beberapa LKS telah menawarkan solusi, hal tersebut seringkali melanggar aturan yang ada. Selain itu, praktik Tabungan Wadi’ah di Bank Umum Syariah (BUS) tidak berbeda signifikan dengan tabungan konvensional, kecuali dalam hal bagi hasil, yang mana BUS masih membebankan nasabah dengan biaya pembukaan rekening.